Banking Financial Performance as Influenced by Credit Risk, Liquidity and Bank Size In Conventional Banks Listed On The Indonesian Stock Exchange For The Period 2014 - 2023 - Kiki Muntaqiah; Akhmadi Akhmadi (Institute of Advanced Knowledge and Science, 2024)
This study aims to empirically examine the impact of credit risk, liquidity, and bank size on the financial performance of conventional banks listed on the Indonesia Stock Exchange (IDX) during the period 2014-2023, with a particular focus on the COVID-19 pandemic period. The research variables used include the Non-Performing Loan (NPL) ratio, Loan to Deposit Ratio (LDR), and bank size, while Return on Assets (ROA) is used as a financial performance indicator. This study uses the purposive sampling method to select a sample from 138 banks listed on the IDX, resulting in 9 banks that meet the established criteria. Data analysis was conducted using panel data regression with the Fixed Effect Generalized Least Square (GLS) model to address the issues of autocorrelation and heteroskedasticity found in classical assumptions. The research results show that credit risk (NPL) has a significant negative impact on ROA, while bank size and liquidity (LDR) have a significant positive impact on ROA during the pandemic. These findings highlight the importance of managing credit and liquidity risks as well as optimizing bank size to improve financial performance amid the challenging economic conditions caused by the pandemic. This study also suggests that the financial performance of banks can be more stable if supported by appropriate risk management strategies and good operational efficiency. The limitations of this study include a sample restricted to conventional banks in Indonesia and the specific conditions during the COVID-19 pandemic, which may affect the generalization of the results.